Bands of brothers - Hanks, Tom; Robinson, Phil Alden; Locraine, Richard (USA : Home Box Office, 2002)
Tells the story of Easy Company, 506th Regiment of the 101st Airborne Division, U.S. Army, an elite rifle company that parachuted into France early on D-Day morning, fought in the Battle of the Bulge, captured Hitler's Eagle's Nest at Berchtesgaden, and suffered heavy casualties. Also includes a documentary about the soldiers in Easy Company
vol.1 Currahe - vol.2 Day of days - vol.5 Crossroads - vol.6 Bastogne - vol.7 The breaking point - vol.8 The patrol - vol.9 Why we fight - vol.10 Points
Part 1-2, 5-10
Editors, Billy Fox ...[et al.] ; music by Michael Kamen ; director of photography, Remi Adefarasin, Joel J. Ransom
Writer, John Orloff
Cast : Kirk Acevedo, Eion Bailey, Michael Cudltz, Dalf Dye
VCD format
Keywords: War films